Preliminary study of traditional selection potato varieties resistance for potatoes ladybug Henosepilachna vigintioctopunctata Motch. (Fabricius, 1775) in the Primorsky territory - N. V. Matsishina (Ovoŝi Rossii, 2019)
Relevance. Potato ladybug is a polyphagous pest. Its distributed throughout the Far East, in India, Korea, Japan and the countries of South America. Most affected by it are potatoes, tomatoes, eggplant, zucchini, peppers, cucumbers, pumpkin, melon, beans. Leaving the veins intact pest eats the soft tissue of the leaf. Such leaves die quickly. Potato ladybug is a carrier of some diseases of potato and it also causes damage to plants. But insecticides pollute products and sustainable insect populations. The use of varieties with high resistance to pest damage eliminates the need for mass application of insecticides.Methods. The data on a preliminary assessment of potato varieties of domestic and foreign selection for resistance to a twenty-eight-point potato ladybug Henosepilachna vigintiomaculata Motch. (Fabricius, 1775) in the Primorye Territory. This work aim work was a preliminary assessment of the traditional potato breeding resistance factors to pest damage. The experiment out using generally accepted methods for the study and evaluation of potato varieties for pests with minor modifications was carried.Results. As a study result it was found that Belmonda, Labella, Red Lady, Queen Anna, Lilly, Sante varieties were the least suitable for passing the stages of ontogenesis and nutritional nutrition of the pest. The most tolerant to the pest – varieties Smak, Casachok, Yantar. The maximum mortality of potato ladybug larvae was observed in varieties Belmonda, Dachny, Augustin, Yubilyar, Labella, Sante, Koroleva Anna, Laperla in laboratory experiment. Minimum on varieties Smak, Casachok, Yantar, Red Lady. The data indicate the manifestation of an antibiotic barrier in potatoes, which must be confirmed by a field experiment.